Ефект кручення чорної діри та її відношення до інформації - Gkigkitzis, I.; Haranas, I.; Cavan, E. (Publishing house "Academperiodika", 2019)
In order to study the effects of the torsion on the gravitation in space-time and its relation to information, we use the Schwarzschild metric, where the torsion is naturally introduced through the spin particle density. In the black hole scenario, we derive an analytic solution for the black hole gravitational radius with the spin included. Then we calculate its entropy in the cases of parallel and antiparallel spins. Moreover, four analytical solutions for the spin density as a function of the number of information are found. Using these solutions in the case of parallel spin, we obtain expressions for the Ricci scalar as a function of the information number N, and the cosmological constant lambda is also revealed.